Diet analysis of the Khuvsgul grayling: (Thymallidae: Thymallus nigrescens) (Mongolian Journal of Geography and Geoecology, 2022)
Lake Khuvsgul has low fish diversity due to its ultra-oligotrophic conditions and contains only 10 fish species. In this study, we examined stomachs of the endemic species, Khuvsgul grayling (Thymallus nigrescens), and compared a diet variation among populations inhabiting littoral and pelagic zones. We collected fish samples from littoral and pelagic zones of the southwest, northwest, and east shores using gill nets, and preserved specimens and their stomachs in 4% formalin. In the laboratory, we weighed fish stomachs and identified organisms in the stomachs at mostly order levels. We then assessed the abundances of each taxonomic group and calculated percentages of their occurrences based on the number of fish specimens caught at each zone. In order to examine whether the diet of the Khuvsgul grayling differs by littoral and pelagic zones, we conducted non-metric multidimensional scaling (NMDS), Analysis of Dissimilarity (ANOSIM), and Similarity Percentage (SIMPER) analyses. All statistical analyses were performed using the vegan package in the R program. According to the results, we found 13 taxonomic groups in the fish stomachs. Among them, zooplankton was the most frequently occurring group in the diet of the pelagic populations, whereas larval dipteran was the most frequently occurring group in the diet of littoral populations. The diet difference between littoral and pelagic populations was statistically significant (ANOSIM: p